Effects of Lithium on Morphine Tolerance Using Analgesia, Nitrite Determination, Histology and Immunohistochemistry of Forehead Cortex in Adult Male Swiss Mice - Saman Barzegar; Tayebeh Noori; Mohammad Hosein Farzaei; Mozafar Khazaei; Samira Shirooie (مجله دانشگاه علوم پزشکی گرگان, 2022)
Background and Objective: Chronic use of opioids leads to analgesic tolerance. Protein kinase C (PKC), adenylyl cyclase (AC), nitric oxide (NO) and glycogen synthase kinase 3 beta (GSK-3β) are involved in morphine tolerance. Lithium activates the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (AKT) pathway that inhibits GSK-3β and reduces morphine-induced tolerance. This study was performed to evaluate the effects of lithium on morphine dependence symptoms and tolerance of its analgesic effects in Swiss mice by GSK-3β signaling. Methods: This experimental study was performed on 56 Swiss male albino mice that were randomly allocated into 8 groups (each containing 7 mice). The intraperitoneal injection of morphine at different concentrations (50, 50 and 75 mg/kg) and different hours (08:00, 11:00 and 16:00, respectively) was performed for 4 days, and a single dose 50 mg/kg was administered on the 5th day. The effects of three doses of lithium (1, 5 and 10 mg/kg) given orally, 45 min before morphine injections on morphine-induced analgesic tolerance were evaluated. To evaluate analgesia latency on day 1, 3 and 5, tail flick and hot plate tests were done. The brain of each animal was removed to measure nitrite levels, and histological evaluation and immunohistochemistry for p-glycogen synthase (p-GSSer640) were performed on the last day of the study. Results: Co-administration of lithium significantly increased the latency of analgesia in comparison with the morphine group on the 3rd and 5th day (P<0.05). Lithium reduced the morphine-induced increase of nitrite levels and also reduced brain damage. In addition, immunohistochemistry assay of p-GSSer640 indicated a significant reduction of the morphine-induced phosphorylation of GS at S640 by GSK in the lithium-treated mice. Conclusion: Lithium administration can reduce morphine tolerance in adult male Swiss mice.